"The second term of a GP is12 more than the first term"
-----> ar - a = 12
"the common ratio is half of the first term" ------> r = a/2 or a = 2r
put that back into ar-a = 12
2r(r) - 2r = 12
r^2 - r - 6 = 0
(r-3)(r+2) = 0
r = 3 or r = -2
if r = 3, the a = 6, third term = ar^2 = 6(9) = 54
if r = -2 ........ (your turn)
The second term of a GP is12 more than the first term,given that the common ratio is half of the first term.Find the third term of the GP?
12 answers
Why did you not finish the mathematics
Thanks a bunch
I can't solve it
The secon term of a GP is 12 more than the first term given that the common ratio is half of the first term find the third term of the GP.
I really love this app and everything that it entails the -2 can't be used as the common ratio because it is negative so the positive one will work perfectly
For r=-2 the answer is-0•75
You are a bonkon,why didn't you finish the solving
good results
T2=12+a
R=1/2 *a
Un=arn-1
12+a=a*1/2a
12+a=a²/2
Multiply both sides by two
24+2a=a²
Rearrange it
a²-2a-24=0
Then factorise.the factors are -6 and 4
a² -6a+4a-24=0
(a²-6a)(4a-24)=0
a(a-6)+4(a-6)
(a+4)(a-6)
a=-4 or a=6
Using the positive answer 6
T2=12+a=12+6=18
r=1/2*a=1/2*6=3
So therefore
T3=arn1
T3=6*3³–¹
T3=6*3²
T3=6*9
T3=54
R=1/2 *a
Un=arn-1
12+a=a*1/2a
12+a=a²/2
Multiply both sides by two
24+2a=a²
Rearrange it
a²-2a-24=0
Then factorise.the factors are -6 and 4
a² -6a+4a-24=0
(a²-6a)(4a-24)=0
a(a-6)+4(a-6)
(a+4)(a-6)
a=-4 or a=6
Using the positive answer 6
T2=12+a=12+6=18
r=1/2*a=1/2*6=3
So therefore
T3=arn1
T3=6*3³–¹
T3=6*3²
T3=6*9
T3=54
I also need an answer to this.
Is this one mad. Finish the solution.💀